Performance evaluation and benchmarking for the era of artificial intelligence : 10th TPC Technology Conference, TPCTC 2018, Rio de Janeiro, Brazil, August 27-31, 2018, Revised selected papers /: 10th TPC Technology Conference, TPCTC 2018, Rio de Janeiro, Brazil, August 27-31, 2018, Revised selected papers. (2019) - Unknown
No abstract available